Pengaruh Metode Eksperimen Terhadap Kemampuan Sains Anak Kelompok B Tk Tunas Harapan 1 Tunggunjagir Kecamatan Mantup Kabupaten Lamongan - Retnaningsih, Lina Eka (JCE (Journal of Childhood Education), 2017)
The purpose of this study is to know the science ability of group B children of Tunas Harapan kindergarten 1 Tunggunjagir Mantup Lamongan before applying experimental method, and to know the science ability of group B children of Tunas Harapan kindergarten 1 Tunggunjagir Mantup Lamongan after applying experimental method. This study uses pre-experimental design with one-group pretest-posttest design. Data collection technique uses observation. The subjects of this study were 16 children. The validity instrument uses the validity construction test, while its reliability uses the observation reliability test with the formula presented by Fernandes. Data obtained in the field were analyzed by using data analysis technique of wilcoxon match pairs test. From the calculation results it is obtained the average scores of pre-test results amounted to 20.8 and the average scores of post-test results amounted to 26.8 with Tcount â¤ Ttable (0 â¤ 21). Thus, it could be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. That means the research hypothesis that there is influence of experimental methods on the science skills of group B children of Tunas Harapan Kindergarten 1 Tunggunjagir district Mantup Lamongan Regency is accepted.